Analysis of whole transcriptome reveals the immune response to porcine reproductive and respiratory syndrome virus infection and tylvalosin tartrate treatment in the porcine alveolar macrophages - Du, Kun; Xia, Yu; Wu, Qian; Yin, Miao; Zhao, Hong; Chen, Xi-wen (Frontiers in Immunology, 2025)
IntroductionPorcine reproductive and respiratory syndrome virus (PRRSV) is a major pathogen that has caused severe economic losses in the swine industry. Screening key host immune-related genetic factors in the porcine alveolar macrophages (PAMs) is critical to improve the anti-virial ability in pigs.MethodsIn this study, an in vivo model was set to evaluate the anti-PRRSV effect of tylvalosin tartrates. Then, strand-specific RNA-sequencing (ssRNA-seq) and miRNA-sequencing (miRNA-seq) were carried out to profile the whole transcriptome of PAMs in the negative control, PRRSV-infected, and tylvalosin tartrates-treatment group.ResultsThe ssRNA-seq identified 11740 long non-coding RNAs in PAMs. Based on our attention mechanism-improved graph convolutional network, 41.07% and 28.59% lncRNAs were predicted to be located in the nucleus and cytoplasm, respectively. The miRNA-seq revealed that tylvalosin tartrates-enhanced miRNAs might play roles in regulating angiogenesis and innate immune-related functions, and it rescued the expression of three anti-inflammation miRNAs (ssc-miR-30a-5p, ssc-miR-218-5p, and ssc-miR-218) that were downregulated due to PRRSV infection. The cytoplasmic lncRNAs enhanced by tylvalosin tartrates might form ceRNA networks with miRNAs to regulate PAM chemotaxis. While cytoplasmic lncRNAs that were rescued by tylvalosin tartrates might protect PAMs via efferocytosis-related ceRNA networks. On the other hand, the tylvalosin tartrates-rescued nuclear lncRNAs might negatively regulate T cell apoptosis and bind to key anti-inflammation factor IL37 to protect the lungs by cis- and trans-regulation.ConclusionsOur data provides a catalog of key non-coding RNAs in response to PRRSV and tylvalosin tartrates and might enrich the genetic basis for future PRRSV prevention and control.